Demographic, Clinical Profile, and Outcome of Guillain-Barré Syndrome Patients in ICU: A Single Center, Retrospective Study - Khanal, Kishor; Poudel, Saroj; Shrestha, Pallawi; Aryal, Sunidhi (Med Phoenix, 2025)
Introduction: Guillain-Barré Syndrome (GBS) is an acute, immune-mediated peripheral neuropathy causing progressive muscle weakness and, in severe cases, respiratory failure requiring intensive care unit (ICU) admission. The study was conducted with the aim to analyze the demographic profile, clinical presentation, treatment modalities, and outcomes of GBS patients admitted to a tertiary-level ICU in Nepal. Materials and Methods: A retrospective study was conducted over five years (January 2020 to December 2024). The data were obtained through the National Intensive Care Registry Foundation (NICRF) platform. Results: A total of 30 patients were included. Males constituted the majority of the study population (83.4%, n=25), with a mean age of 52.97 years (SD=22.36), mostly in the age group of 61–80 years. Clinically, 83.3% (n=25) presented with progressive limb weakness, while 23% (n=7) had sensory deficits or other symptoms. Acute inflammatory demyelinating polyradiculoneuropathy (AIDP) was present in 50% (n=15) of patients, followed by acute motor axonal neuropathy (AMAN) 26.7% (n=8), acute motor and sensory axonal neuropathy (AMSAN) 13.3% (n=4), and Miller Fisher Syndrome 10% (n=3). Respiratory tract infections 23.3% (n=7) and diarrhea 16.67% (n=5) were the most common antecedent events. Treatment primarily involved intravenous immunoglobulin (IVIg) 66.67% (n=20), while 33.33% (n=10) required mechanical ventilation (mean duration 8.5 days). Mortality rate was 6.7% (n=2). Conclusion: This study shows a male predominance, with AIDP as the primary GBS subtype. The most common type of treatment administered was intravenous immunoglobulin (IVIG).